2011
DOI: 10.1210/jc.2010-1835
|View full text |Cite
|
Sign up to set email alerts
|

Hyperadiponectinemia Is Independent of Kidney Function, Diabetes Duration, and Control in Type 1 Diabetic Patients without Microangiopathy

Abstract: In T1D without microangiopathy, high ADPN levels could not be related to anthropometric diabetes parameters, kidney function, or high insulin levels. The nature of this elevation remains unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…This finding may be explained by the greater stability of HbA1c level, which is also independent from transient confounders, as postprandial state, which significantly affect random glucose level. Similar association between elevated serum adiponectin concentration and HbA1c or hyperglycemia has been reported in other studies [ 1 ], although not equivocally [ 3 ]. Higher serum adiponectin concentration in patients with diabetic ketoacidosis at onset of T1DM may be attributed to the rise of adiponectin in conditions associated with increased catabolism and cachexia.…”
Section: Discussionsupporting
confidence: 88%
“…This finding may be explained by the greater stability of HbA1c level, which is also independent from transient confounders, as postprandial state, which significantly affect random glucose level. Similar association between elevated serum adiponectin concentration and HbA1c or hyperglycemia has been reported in other studies [ 1 ], although not equivocally [ 3 ]. Higher serum adiponectin concentration in patients with diabetic ketoacidosis at onset of T1DM may be attributed to the rise of adiponectin in conditions associated with increased catabolism and cachexia.…”
Section: Discussionsupporting
confidence: 88%
“…12,14 In the FinnDiane study, Forsblom et al 13 demonstrated that high adiponectin levels were associated with 11-year risk of all-cause and cardiovascular mortality in a nationwide multicenter cohort of Finnish adults with T1DM. Hypotheses to explain elevated adiponectin levels in patients with T1DM include a compensatory response to vascular injury, 24 decreased clearance due to renal insufficiency, 14 effects of subcutaneous insulin treatment, 25 and posttranslational modifications (glycosylation) that could occur in persons with T1DM.…”
Section: Discussionmentioning
confidence: 99%
“…Total and high-molecular-weight adiponectin levels are elevated in the serum of T1D patients, but there are lower levels of adiponectin receptor expression on monocytes and antigen-presenting cells, which may be responsible for increased inflammation. [1][2][3][4][5] In contrast, lower serum levels of adiponectin are associated with T2D, cardiovascular disease, and insulin resistance, although the levels increase when T2D patients undergo post-gastric bypass surgery for visceral fat reduction. 6,7 The downregulation of adiponectin receptor expression in T1D patients is associated with the proliferation of primary CD4 + T-cells in the presence of islet lysate independent of adiponectin treatment, whereas healthy control T-cells are inhibited by adiponectin.…”
Section: Introductionmentioning
confidence: 99%